2015
DOI: 10.1037/lhb0000095
|View full text |Cite
|
Sign up to set email alerts
|

Suspect filler similarity in eyewitness lineups: A literature review and a novel methodology.

Abstract: Eyewitness lineups typically contain a suspect (guilty or innocent) and fillers (known innocents). The degree to which fillers should resemble the suspect is a complex issue that has yet to be resolved. Previously, researchers have voiced concern that eyewitnesses would be unable to identify their target from a lineup containing highly similar fillers; however, our literature review suggests highly similar fillers have only rarely been shown to have this effect. To further examine the effect of highly similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
56
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 48 publications
(76 reference statements)
10
56
4
1
Order By: Relevance
“…Further, Malmberg and Xu (2007) found that when associative recognition tests feature both high-and low-similarity fillers, participants made less use of recollection than when target-filler similarity was uniformly high. Typically, target-filler similarity is not uniform across lineup members and reviews of lineup similarity effects (e.g., Fitzgerald et al, 2015) and empirical tests of the 'dud effect' (Charman, Wells, & Joy, 2011) demonstrate patterns like those found in associative recognition. That is, when simultaneous lineups include some fillers with relatively lower similarity to the offender, eyewitnesses mistakenly anticipate that distinguishing a guilty suspect will be relatively easy and are more likely to mistakenly identify an innocent suspect who closely resembles the offender than when targetfiller similarity is uniformly high.…”
Section: Identification Biasmentioning
confidence: 99%
“…Further, Malmberg and Xu (2007) found that when associative recognition tests feature both high-and low-similarity fillers, participants made less use of recollection than when target-filler similarity was uniformly high. Typically, target-filler similarity is not uniform across lineup members and reviews of lineup similarity effects (e.g., Fitzgerald et al, 2015) and empirical tests of the 'dud effect' (Charman, Wells, & Joy, 2011) demonstrate patterns like those found in associative recognition. That is, when simultaneous lineups include some fillers with relatively lower similarity to the offender, eyewitnesses mistakenly anticipate that distinguishing a guilty suspect will be relatively easy and are more likely to mistakenly identify an innocent suspect who closely resembles the offender than when targetfiller similarity is uniformly high.…”
Section: Identification Biasmentioning
confidence: 99%
“…Additionally, relative risk ratios were calculated to compare the diagnosticity of the lineup procedures to determine if they were significantly different from each other. Fitzgerald and Price (2015) suggest that the relative risk ratios are beneficial, as they have known sampling distributions and established methods of computing confidence intervals. The risk ratio was calculated in a similar way to the DR whereby the number of suspect identifications was divided by the total number of identifications (divided by 6, as there was no designated innocent suspect).…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…One major challenge that has appeared within the foil similarity literature is that researchers seem to be having difficulty conceptualizing what constitutes as high, moderate, and low similarity. It is possible that this challenge is occurring because researchers are trying to take a concept that is measured on a continuum and attempting to break it down into distinct categories (i.e., low vs. high; Fitzgerald et al, 2015). For example, in the current study and in Fitzgerald et al (2015) the photograph ratings used for the construction of the high similarity lineups had mean similarity ratings around the mid-point of the similarity scale (current study: M = 4.49 on a scale of 1 to 10).…”
Section: Foil Similaritymentioning
confidence: 99%
See 2 more Smart Citations